Effects of The Japan Disaster 2011 on the Stock Return and Trading Volume in Indonesia Stock Exchange - Sulistyo Wahyu Wijanarko; Bachruddin Bachruddin (Al Tijarah, 2015)
This study aims to analyze international disaster event on the capital market activities, especially on the Indonesia Stock Exchange. Researcher analyzed the market reaction to the Japan disaster on March 11, 2011. This research using the data 45 companies (LQ-45) in Indonesia Stock Exchange and the event date is ten days before and ten days after the disaster. From the analysis showed that the event is not signifi cantly affecting the stock return and trading volume activity between pre and post the event. These result indicate that the Japan disaster give no impact to the investor on Indonesia Stock Exchange.